À la discrétion du conseiller ? - Hadrien Clouet (Temporalités)
As jobseekers receive support from the specific institutions for unemployed, they have to comply with regular interaction with their caseworkers. These interactions articulate three temporalities: a rhythm, an appointment schedule and a duration. The article builds on the observation of interviews between jobseekers and their caseworkers in several employment agencies (two Pôle emploi agencies in France, an Arbeitsagentur and a Jobcenter in Germany) to explore the discretionary power of caseworkers, as well as the rooms for maneuver of the audience targeted. This perspective identifies the relationship between jobseekers and caseworkers with a process of temporal adjustment or conflict. It shows how the administrative temporalities of unemployment are unequally controlled and disputed during the interviews, with different outcomes in each institution. The discretionary power of advisors is particularly high concerning the frequency of interviews. But Arbeitsagentur’s jobseekers have resources to discuss schedules, as do Pôle emploi’s jobseekers to challenge durations. By contrast, assisted jobseekers in Jobcenters seem significantly deprived in these administrative temporal struggles.